Green and rapid mechanosynthesis of high-porosity NU- and UiO-type metal–organic frameworks. Issue 51 (29th May 2018) - Fidelli, Athena M.; Karadeniz, Bahar; Howarth, Ashlee J.; Huskić, Igor; Germann, Luzia S.; Halasz, Ivan; Etter, Martin; Moon, Su-Young; Dinnebier, Robert E.; Stilinović, Vladimir; Farha, Omar K.; Friščić, Tomislav; et al.
Abstract : Dodecanuclear zirconium precursor enables a rapid and efficient mechanochemical synthesis of advanced MOFs NU-901 and UiO-67 with surface areas of up to 2250 m 2 g −1 . Abstract : The use of a dodecanuclear zirconium acetate cluster as a precursor enables the rapid, clean mechanochemical synthesis of high-microporosity metal–organic frameworks NU-901 and UiO-67, with surface areas up to 2250 m 2 g −1 . Real-time X-ray diffraction monitoring reveals that mechanochemical reactions involving the conventional hexanuclear zirconium methacrylate precursor are hindered by the formation of an inert intermediate, which does not appear when using the dodecanuclear acetate cluster as a reactant.